Evaluating the Uncertainty of Terrestrial Water Budget Components Over High Mountain Asia - Yoon, Yeosang; Kumar, Sujay V.; Forman, Barton A.; Zaitchik, Benjamin F.; Kwon, Yonghwan; Qian, Yun; Rupper, Summer; Maggioni, Viviana; Houser, Paul; Kirschbaum, Dalia; Richey, Alexandra; Arendt, Anthony; et al. (Frontiers in Earth Science, 2019)
This study explores the uncertainties in terrestrial water budget estimation over High Mountain Asia (HMA) using a suite of uncoupled land surface model (LSM) simulations. The uncertainty in the water balance components of precipitation (P), evapotranspiration (ET), runoff (Q), and terrestrial water storage (TWS) is significantly impacted by the uncertainty in the driving meteorology, with precipitation being the most important boundary condition. Ten gridded precipitation datasets along with a mix of model-, satellite-, and gauge-based products, are evaluated first to assess their suitability for LSM simulations over HMA. The datasets are evaluated by quantifying the systematic and random errors of these products as well as the temporal consistency of their trends. Though the broader spatial patterns of precipitation are generally well captured by the datasets, they differ significantly in their means and trends. In general, precipitation datasets that incorporate information from gauges are found to have higher accuracy with low Root Mean Square Errors and high correlation coefficient values. An ensemble of LSM simulations with a selected subset of precipitation products is then used to produce estimates of terrestrial water budget components and their associated uncertainties. The mean annual estimates of the surface mass (water) balance components from this model ensemble are comparable to global estimates from prior studies, whereas the uncertainty/spread of P, ET, and Q is significantly larger than the corresponding estimates from global studies. A comparison of evapotranspiration, snow cover fraction, and changes in terrestrial water storage estimates against remote sensing-based reference datasets confirms the significant role of the input meteorology in influencing the water budget characterization over HMA and points to the need for improving meteorological inputs.